Association between stress hyperglycemia ratio (SHR) and the risk of acute kidney injury in patients with chronic kidney disease: analysis of the MIMIC-IV database - Jinliang Li; Lianqu Wang; Jiule Zhang; Xiaoguang Li; Zhiling Jiao (BMC Nephrology)
Abstract Background Stress hyperglycemia ratio (SHR) is a novel indicator used to evaluate the severity of SH. This study aimed to explore the association between SHR and the risk of AKI and death among individuals with chronic kidney disease (CKD). Methods This retrospective cohort investigation sourced data from the Medical Information Mart for Intensive Care-IV (MIMIC IV2.2) repository. The primary endpoint was AKI incidence, while secondary endpoints included in-hospital mortality and renal replacement therapy (RRT). The correlation of SHR with the likelihood of AKI in CKD patients was assessed utilizing restricted cubic spline (RCS) and Cox proportional hazards models. Then using Kaplan-Meier survival curves to analyze endpoint differences across varying SHR levels. Results Among 2,500 CKD patients, 795 (31.8%) developed AKI during hospitalization. Cox proportional hazards analysis indicated a positive association between SHR and AKI incidence. The RCS model showed an approximately linear relationship, with higher SHR linked to increased AKI risk. In addition, Kaplan-Meier survival analysis unveiled notable distinctions in three endpoints across cohorts of patients characterized by varying SHR levels. Conclusions SHR emerges as a dependable and autonomous indicator for predicting AKI occurrence and unfavorable renal outcomes in individuals with CKD. Clinical trial number Not applicable.